Implementation of Islamic Spiritual Guidance for People with Mental Disorders at the Jalma Sehat Kudus Foundation - Bastomi, Hasan (IAIN Kudus, 2021)
Implementation of Islamic Spiritual Guidance for People with Mental Disorders at the Jalma Sehat Kudus Foundation. This study aims to reveal the implementation of Islamic spiritual guidance for people with mental disorders at the Jalma Sehat Kudus Foundation. This research on the implementation of Islamic spiritual guidance for people with mental disorders was carried out using a qualitative approach with the type of field research (field research) with data collection techniques using Interview, Observation and Documentation. The research subjects or informants in this research are the Chairperson of the Jalma Sehat Kudus Foundation, nurses, and spiritual mentors of the Jalma Sehat Kudus Foundation. The results showed that the Jalma Sehat Kudus Foundation in carrying out spiritual guidance for people with mental disorders. Methods. Spiritual guidance for people with mental disorders was carried out by the individual method (direct) and the group guidance method. The stages and materials for spiritual guidance for people with mental disorders are in three stages, namely: (1) the initial stage is by introducing Fiqh Worship, (2) the intermediate stage is the seriousness stage, namely by providing religious lecture guidance, and the final stage is the stage of ending the guidance process ( termination). Suggestion It is necessary to have a permanent spiritual guide who is assigned to carry out spiritual guidance at the Jalma Sehat Kudus Foundation so that the implementation of Islamic spiritual guidance can run continuously.Keywords: Guidance, Islamic Spirituality, Mental Disorders